Stock Market Equilibrium and Macroeconomic Fundamentals - Leigh, Lamin (IMF Working Papers; Working Paper ;, 1997)
This paper examines the efficiency of the Stock Exchange of Singapore and the relationship between the stock market and the overall economy. Using a wide range of methods for testing market efficiency, the paper establishes that the Singapore stock market is both 'weakly' and 'semi-strongly' efficient in asset-pricing terms but not 'strongly' efficient. Granger causality tests based on the efficiency test results indicate that developments in the stock market appear to be systematically related to the overall economy in Singapore and can thus serve as a leading indicator of its intertemporal behavior.